Predictors of Developing Significant Mitral Regurgitation Following Percutaneous Mitral Commissurotomy with Inoue Balloon Technique. (15th August 2011) - Elasfar, Abdelfatah A.; Elsokkary, Hatem F.
Abstract : Background . Despite the high technical expertise in percutaneous mitral commissurotomy (PMC), mitral regurgitation (MR) remains a major procedure-related complication. The aim of this work is to find out the most sensitive and applicable predictors of development of significant mitral regurgitation (SMR) following percutaneous mitral commissurotomy using Inoue balloon technique. Methods . We studied prospectively the preprocedural (clinical, echocardiography, and hemodynamic) and procedural predictors of significant mitral regurgitation (identified as increase of ≥2/4 grades of pre-PMC MR by color Doppler flow mapping) following valvuloplasty using Inoue balloon in 108 consecutive patients with severe mitral stenosis. Multiple stepwise logistic regression analysis was performed for variables found positive on univariate analysis to determine the most important predictor(s) of developing SMR. Results . The incidence of SMR following PMC using Inoue technique was 18.5% (10 patients). MV scoring systems were the only variables that showed significant differences between both groups (Group A without SMR and Group B with SMR). However, no clinical, other echocardiographic measurements, hemodynamic or procedural variables could predict the development of SMR. Using multiple regression analysis, the best predictive factor for the risk of SMR after Inoue BMV was the total MR-echo score with a cutoff point of 7 and a predictive percentage of 97.7%. Conclusions . The total MR-echo score is the only independent predictor of SMR following PMC using Inoue technique with a cutoff point of 7.